An investigation of the region of DNA required for Streptocymes Penemafaciens plasmid pSPN1 replication - Smith, Anthony (Department of Molecular and Cell Biology, 2016)
Plasmid pSPNl is a 26.5kb cryptic plasmid, originally isolated from Streptomyces penemafaciens ATCC 31599. A 12.5kb BglII fragment of pSPNl was cloned into the vector pLR2, and this conferred on pLR2 which lacks a Streptomyces origin of replication, the ability to replicate in a number of Streptomyces species. A vector pBlue was constructed by inserting a streptomycin resistance gene from plasmid pIJ4642 into the ampicillin resistance gene of the vector Bluescript. The resistance gene was able to function in both E.coli and Streptomyces species and thus pBlue could serve as a vector for shortening and sequencing in E. coli as well as a origin-probe vector in Streptomyces. The origin-containing BglII fragment of pSPNl was cloned into pBlue to create pFull, which was able to be selected for and replicate in Streptomyces. The conditions affecting selection of pFull in Streptomyces were investigated and optimized. The copy number of pFull was found to be 0.2 per chromosome. Attempts were made to clone origin-containing fragments smaller than the 12.5kb BglII fragment. Initially a Sau3A partial library was made of the origin-containing fragment, this however did not produce any replicating plasmids. As an alternative approach, pFull was extensively mapped and a series of deletion derivatives were constructed. The derivatives were tested for the ability to replicate in Streptomyces. Judging from the deletions that were and were not able to replicate it is apparent that at least 5.5kb of DNA is required for pFull and hence for pSPNl to replicate.